2008
DOI: 10.1016/j.seppur.2008.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyaluminum chloride on enhanced softening for the typical organic-polluted high hardness North-China surface waters

Abstract: a b s t r a c tThe treatment of organic-polluted high hardness surface water by enhanced softening via precipitation using various coagulants, such as FeCl 3 , AlCl 3 and polyaluminum chloride (PACl), was investigated in bench scale experiments. Higher removal of natural organic matter (NOM) (UV 254 removal reaches about 50%) is achieved by enhanced softening with coagulant addition conditions as compared with conventional coagulation at natural pH or by softening alone without coagulation. It is found that PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…Similar results are obtained by Yan et al (2008) who studied the treatment of organic-polluted high hardness surface water using enhanced softening via precipitation employing different coagulants, such as FeCl3, AlCl3 and polyaluminum chloride (PACl), in bench scale experiments. Higher elimination of natural organic matter (NOM) (UV254 removal attained ~50%) was obtained under enhanced softening with coagulant injection conditions as compared with conventional coagulation at natural pH or by softening alone without coagulation.…”
Section: Om Removal Under Softening Conditionssupporting
confidence: 80%
“…Similar results are obtained by Yan et al (2008) who studied the treatment of organic-polluted high hardness surface water using enhanced softening via precipitation employing different coagulants, such as FeCl3, AlCl3 and polyaluminum chloride (PACl), in bench scale experiments. Higher elimination of natural organic matter (NOM) (UV254 removal attained ~50%) was obtained under enhanced softening with coagulant injection conditions as compared with conventional coagulation at natural pH or by softening alone without coagulation.…”
Section: Om Removal Under Softening Conditionssupporting
confidence: 80%
“…The treatment of organic-polluted high-hardness surface water by enhanced softening via precipitation using PACl, FeCl 3 and AlCl 3 has been investigated and reported in our previous paper [25]. It is found that higher removal of natural organic matter (NOM) (UV 254 removal reaches about 50%) is achieved by enhanced softening with PACl addition as compared with conventional coagulation at natural pH or by softening alone without coagulation.…”
Section: Enhanced Softening With Coagulantmentioning
confidence: 99%
“…The performance of enhanced softening is affected significantly by magnesium content in raw water [25]. For water with higher content of Mg 2+ , the inflexion pH for favorable NOM removal is lower.…”
Section: Enhanced Softening With Coagulantmentioning
confidence: 99%
“…So far, various methods, including adsorption (6), ion exchange (8), nanophotocatalysis (9), membrane (10,11) and ultrasonic technologies (11), electrocoagulation (12), coagulation and enhanced coagulation (13) have been employed for the removal of humic substances from water, among which the advanced oxidation processes (AOPs) have been introduced as a suitable option for the removal or destruction of the humic substances compared to other common methods (coagulation, ion exchange, membrane filtration, and adsorption) (6). Synthesis of hydroxyl radicals with high oxidative power in AOP has caused these treatment processes to be known as one of the most practical physicochemical treatment procedures (14).…”
Section: Introductionmentioning
confidence: 99%